Distributive leadership: a strategy to develop more and better organizational capacities in educational institutions - Maureira Cabrera, Óscar (2018)
A diversity of studies, reflections and policies in these last two decades have highlighted the relevance and relevance of leadership in schools as a critical factor of quality and equity, regardless of the sociocultural context and school organization modalities for the development of school institutions. Thus, the present review work, framed in content analysis, describes, analyzes and discusses the main practical dimensions of managerial leadership, its criticisms and limitations, as well as exposes the perspective of distributive leadership as a key approach and strategy to consider to advance both in the knowledge of this polysemic construct, as well as in its transfers and strategies for the sustainable improvement of learning in the school organization. As a key result of this review, emerging as a focus of analysis of leadership practices, both for research and for different application perspectives, the characteristics and effects of the interaction between leader, collaborators and situation.